2020
DOI: 10.1155/2020/4201945
|View full text |Cite
|
Sign up to set email alerts
|

Research on Ecological Restoration Mechanism of Rare‐Earth Mines Based on Evolutionary Game

Abstract: With the continuous improvement of the rare earth’s international status, the status of rare Chinese earth has gradually become prominent all over the world. When China enjoys the advantages of large reserves of rare-earth resources, at the same time, Chinese rare-earth enterprises are lagging in technology and lacking innovation capabilities. The rare-earth industry is mainly concentrated on the separation and smelting process, which has an indelible impact on the ecological environment around the mine. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The relevant stakeholders of carbon offsetting of mineral resources include the central government, local governments, central enterprises, local enterprises, and rural residents [23,24]; two or three of them can be selected to construct a game model. Studies have shown that, under government supervision, increasing subsidies to carbon offsetting enterprises can motivate them to conduct carbon offsetting work [25][26][27]. Research on tourism carbon offsetting mainly includes matrix games that revolve around the government, residents, and tourism enterprises to analyze game behavior [28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relevant stakeholders of carbon offsetting of mineral resources include the central government, local governments, central enterprises, local enterprises, and rural residents [23,24]; two or three of them can be selected to construct a game model. Studies have shown that, under government supervision, increasing subsidies to carbon offsetting enterprises can motivate them to conduct carbon offsetting work [25][26][27]. Research on tourism carbon offsetting mainly includes matrix games that revolve around the government, residents, and tourism enterprises to analyze game behavior [28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%